Performance of UVC irradiation with dean vortex technology on clear and turbid tamarind (Tamarindus indica l.) juice - Mohd Hanif, Hani Afiffa (2016)
Tamarind juice is commonly treated by thermal treatment to inactivate microorganisms. However, thermal treatment causes changes in appearance and taste of tamarind juice. Ultraviolet (UV) irradiation has emerged as an alternative to thermal processing. Nonetheless, the application of UV irradiation on tamarind juice is not sited in the literature. In addition, the implementation of UV system with Dean Vortex technology are still limited. Therefore, the present study was aimed to investigate the performance of UVC irradiation on the quality and microbial reduction of clear and turbid tamarind juice. Results of microbiological analyses showed that UVC dosage of 35 mJ/cm2 was found effective in reducing microbial load to a 5-log reduction. The survival curves of viable bacteria (Escherichia coli and native microflora) were best-fitted with the log linear with tailing model (R2 =0.999). UVC treatment significantly reduced the total soluble solids of tamarind juice by 18-21% (p<0.05) but successfully retains the pH, titratable acidity and colour of tamarind juices (p>0.05). Differences in turbidity were significant in UVCtreated clear tamarind juice as UVC dosage increases. Dean Vortex technology was able to reduce the influence of turbidity in UV treatment. In comparison to thermal treatment, the inactivation of microbes by UVC treatment were not as efficient. Thermally treated juice exerted a good resemblance to UVC-irradiated juice in terms of pH, titratable acidity and colour. It also retained the total soluble solids of tamarind juice better than UVC-irradiated juice. Nonetheless, the differences in turbidity were significant (p<0.05) after thermal treatment especially in clear tamarind juice. During seven weeks of storage, the pH of tamarind juices had changed significantly (p<0.05). Total soluble solids had increased (p<0.05) in clear tamarind juice after storage period. The titratable acidity of thermally-treated clear tamarind juice had increased from 0.43% to 0.48% (p<0.05) whereas the titratable acidity of UVC-irradiated turbid tamarind juice decreased from 0.40% to 0.30% (p<0.05). In terms of turbidity, UVC-treated juices showed the lowest turbidity values compared to fresh and thermally-pasteurised juice after seven weeks. On the other hand, there were no effects of different treatments on the lightness, hue angles and chroma after seven weeks of storage. UVC-treated juice exerted the lowest overall changed in colour throughout seven weeks of storage. From microbial analysis, UVC-treated juice showed good stability of viable bacteria during storage. Nonetheless, tamarind juice was spoiled due to outgrowth of yeast and mould after two weeks. Contradictory, thermal treatments successfully retained microbial loads to below detection level during refrigerated storage. In conclusion, the existing UVC treatment may not be a suitable alternative in replacing thermal pasteurisation especially for long-term storage.